Selection and Monetary Non-Neutrality in Time-Dependent Pricing Models - Carlos Carvalho; Felipe Schwartzman (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2014)
For a given frequency of price changes, the real effects of a monetary shock are smaller if adjusting firms are disproportionately likely to have last set their prices before the shock. This type of selection for the age of prices provides a complete characterization of the nature of pricing frictions in time-dependent sticky-price models. In particular: 1) The Taylor (1979) model exhibits maximal selection for older prices, whereas the Calvo (1983) model exhibits no selection, so that real effects are smaller in the former than in the latter; 2) Selection is weaker and real effects of monetary shocks are larger if the hazard function of price adjustment is less strongly increasing; 3) Selection is weaker and real effects are larger if there is sectoral heterogeneity in price stickiness; 4) Selection is weaker and real effects are larger if the durations of price spells are more variable.
Keywords: E10; E30; 330; price setting; monetary non-neutrality; general hazard function; selection effect; heterogeneity